Work-Life Balance as A Mediator Between Digitalization, Burnout, and Job Satisfaction - Aulia Zahra; Setiani Setiani (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2025)
This study aims to determine the effect of Digitalization and Burnout on Job Satisfaction and the mediating role of Work-Life Balance. This research was conducted using quantitative techniques, and explanatory analysis was used to analyze the data that had been collected. The research was conducted at Malang City and Regency's Human Resources Development Staffing Agency (BKPSDM). The population and sample in this study were 90 ASN employees, and the saturated technique was used as a sampling technique. SmartPLS 3.0 is used to process the collected data. This study found that digitalization and Burnout insignificantly impact job satisfaction. However, work-life balance has a positive and significant impact on job satisfaction. Then, the digitalization of job satisfaction can be mediated by work-life balance. Furthermore, the effect of Burnout on job satisfaction can be mediated by job satisfaction.